Factors Associated with Duration time Rehabilitation of Stroke Patient in Community Buriram Province - Phanram, Metha; Singsalasang, Atthawit; Nguanjairak, Rachanond (Journal of The Royal Thai Army Nurses, 2023)
The purposes of this research was to investigate factors associated with duration time rehabilitation of stroke patient in community Buriram Province. This research was retrospective study. The sample consisted of 168 people of stroke patients they were selected by stratified random sampling. The instrument consisted of : (1) the problems questionnaires for stroke patient (2) the National Institutes of Health Stroke Scale (NIHSS) and (3) the questionnaires duration time of rehabilitation for stroke patien. The cronbach alpha reliability coefficients of questionnaires were .99, .86 and .86 respectively. Data collected by questionnaires. Research data were analyzed by both descriptive statistic (percentage, mean and standard deviation) and multiple logistic regression analysis. The results of this research showed that the severity level of stroke patient 43.50% at moderate stroke level. Duration time of rehabilitation 49.40% rehabilitation leesthan 6 month. factors associated with duration time rehabilitation of stroke patient furthermore showed that stroke patient without body paralysis had rehabilitation as 5.08 time respectively in 6 month than stroke patient with body paralysis, duration time of stroke lessthan morethan 12 month had rehabilitation as 1.63 time respectively in duration time of stroke morethan 12 month and stroke patient less mental problem had rehabilitation morethan hight mental problem as 3.57 time respectively in stroke patient. Therefore, Duration time of rehabilitation appropriate, caregive considerate to care stroke patient in first period for the best body rehabilitation and focus mental caring patient for normal or approximaly functional for the fast body recovery and the best recovery efficiency.